Improving Students’ Vocabulary Mastery by Using ESA (Engage, Study, Activate) Method for the Students’ of Eighth Grade at MTs Negeri 02 Pekanbaru - Herdi Herdi; Siti Restian Ningsih (ELT-Lectura, 2018)
This research was conducted at MTs Negeri 2 Pekanbaru based on phenomenon that most of the students were less vocabulary. The purpose of this research was to improve the students’ vocabulary mastery by using ESA (Engage, Study, Activate) method as a teaching method and factor that influence it. The research was a Classroom Action Research. The total number of the sample was 30 students at grade VIII.1 of MTs Negeri 2 Pekanbaru. The researcher did the research in one cycle (five meetings including the test). The data was collected by using vocabulary test, observation checklist, and field notes. There was improvement from based score to cycle 1. In the based score, noun was 65.32, verb was 69.32, adjective 65.32, and adverb was 66.64 with average score 66.67. The result of cycle 1, noun 74.64, and verb was 81.32, adjective was 76.64, and adverb was 82.This research, showed that there were some factors influencing their improvement. The students were engaged in activities, having fun, and active in learning process. The teacher’s approach in explaining material was clear enough and classroom condition as well as method supported the learning achievement. After conducting this research by using ESA (Engage, Study, Activate) method improved in cycle 1. Referring to the result, researcher concluded that ESA (Engage, Study, Activate) method can improve the students’ vocabulary mastery.